Online English Class in Pandemic Time: A Learning Challenge - Muhammad Alfi Khoiruman (Channing : Journal of English Language Education and Literature, 2021)
Learning English before and after the Covid-19 pandemic shows a very different process. Face to face in schools in Indonesia has turned into a learning process entitled Learning From Home (LFH). Moreover, the Ministry of Education and Culture has issued Circular Letter Number 15 of 2020 which contains Guidelines for Learning from Home related to the intensity of increasing the number of residents who are indicated positive for Covid-19. This study aims to describe the challenges faced by teachers and students of grade 6 elementary schools in implementing online learning of English. The case study is applied in this study by direct observation of online learning that occurs in State Elementary Schools (SDN) in the Banyuwangi area; documentation of student learning materials, assignments, and projects; and interviews. The results of the study indicate that the challenges faced include the economics of students related to the difficulty of procuring mobile phones with certain specifications to support learning and the provision of quotas, networks, time, learning supplement materials, and the very diverse abilities of students.